A fatigue crack initiation and growth life estimation method in single-bolted connections. (February 2019) - Jirandehi, Arash P; Chakherlou, TN
Fatigue life estimation accuracy of mechanical parts and assemblies has always been the source of concern in different industries. The main contribution of this article lies in a study on the accuracy of different multiaxial fatigue criteria, proposing and investigating the accuracy of four optimized fatigue crack initiation life estimation methods—volume, weighted volume, surface and point, thereby improving the multiaxial fatigue life estimation accuracy. In order to achieve the goal, the fatigue lives of bolt clamped specimens, previously tested under defined experimental conditions, were estimated during fatigue crack initiation and fatigue crack growth and then summed together. In the fatigue crack initiation part, a code was written and used in the MATLAB software environment based on critical plane approach and the different multiaxial fatigue criteria. Besides the AFGROW software was utilized to estimate the crack growth share of fatigue life. Experimental and numerical results showed to be in agreement. Furthermore, detailed study and comparison of the results with the available experimental data showed that a combination of Smith–Watson–Topper approach and volume method results in lower error values, while a combination of Fatemi–Socie criterion and surface or point method presents estimated lives with lower error values. In addition, the numerical proposed procedure resulted in a good prediction of the location of fatigue crack initiation.